JORNALISMO: TRAJETÓRIA, CRISES E O FENÔMENO DO METRO - Canamary, Mariana Lima Sousa (2010)
The purpose of this research was to analyze a double crisis in Journalism both financial and paradigmatic which has reflected on the process of journalistic mutation observed in some current vehicles, such as the free newspaper Metro, our object of study. We have sought to understand how current characteristics such as news superficiality, speed, instantaneousness, the remarkable presence of publicity and the straightforward appeal to consumption are present in current printed journalism. First, a literature review on Journalism path, history and crisis faced over the last decades has been done. Next, an exploratory research on Metro, the studied object, has been carried out in order to evaluate the presence of characteristics which make it a current vehicle, reflecting a journalistic mutation. The review has showed the existence of a conceptual crisis, aggravated by the economic disruption and marked by the crisis in capital laws.(AU)